Intraspecies Polymorphism of Cryptosporidium parvum Revealed by PCR-Restriction Fragment Length Polymorphism (RFLP) and RFLP-Single-Strand Conformational Polymorphism Analyses - Wu, Zhiliang (American Society for Microbiology, 2003)
A glycoprotein (Cpgp40/15)-encoding gene of Cryptosporidium parvum was analyzed to reveal intraspecies polymorphism within C. parvum isolates. Forty-one isolates were collected from different geographical origins (Japan, Italy, and Nepal) and hosts (humans, calves, and a goat). These isolates were characterized by means of DNA sequencing, PCR-restriction fragment length polymorphism (PCR-RFLP), and RFLP-single-strand conformational polymorphism (RFLP-SSCP) analyses of the gene for Cpgp40/15. The sequence analysis indicated that there was DNA polymorphism between genotype I and II, as well as within genotype I, isolates. The DNA and amino acid sequence identities between genotypes I and II differed, depending on the isolates, ranging from 73.3 to 82.9% and 62.4 to 80.1%, respectively. Those among genotype I isolates differed, depending on the isolates, ranging from 69.0 to 85.4% and 54.8 to 79.2%, respectively. Because of the high resolution generated by PCR-RFLP and RFLP-SSCP, the isolates of genotype I could be subtyped as genotypes Ia1, Ia2, Ib, and Ie. The isolates of genotype II could be subtyped as genotypes IIa, IIb, and IIc. The isolates from calves, a goat, and one Japanese human were identified as genotype II. Within genotype II, the isolates from Japan were identified as genotype IIa, those from calves in Italy were identified as genotype IIb, and the goat isolate was identified as genotype IIc. All of the genotype I isolates were from humans. The Japanese isolate (code no. HJ3) and all of the Nepalese isolates were identified as genotypes Ia1 and Ia2, respectively. The Italian isolates were identified as genotype Ib, and the Japanese isolate (code no. HJ2) was identified as genotype Ie. Thus, the PCR-RFLP-SSCP analysis of this glycoprotein Cpgp40/15 gene generated a high resolution that has not been achieved by previous methods of genotypic differentiation of C. parvum.